Eukaryotic algal community composition in tropical environments from solar salterns to the open sea - Eckmann, Charlotte A.; Eberle, Jessica S.; Wittmers, Fabian; Wilken, Susanne; Bergauer, Kristin; Poirier, Camille; Blum, Marguerite; Makareviciute-Fichtner, Kriste; Jimenez, Valeria; Bachy, Charles; Vermeij, Mark J. A.; Worden, Alexandra Z. (Frontiers in Marine Science, 2023)
Tropical environments with unique abiotic and biotic factors—such as salt ponds, mangroves, and coral reefs—are often in close proximity. The heterogeneity of these environments is reflected in community shifts over short distances, resulting in high biodiversity. While phytoplankton assemblages physically associated with corals, particularly their symbionts, are well studied, less is known about phytoplankton diversity across tropical aquatic environments. We assess shifts in phytoplankton community composition along inshore to offshore gradients by sequencing and analyzing 16S rRNA gene amplicons using primers targeting the V1-V2 region that capture plastids from eukaryotic phytoplankton and cyanobacteria, as well as heterotrophic bacteria. Microbial alpha diversity computed from 16S V1-V2 amplicon sequence variant (ASV) data from 282 samples collected in and around Curaçao, in the Southern Caribbean Sea, varied more within the dynamic salt ponds, salterns, and mangroves, compared to the seemingly stable above-reef, off-reef, and open sea environments. Among eukaryotic phytoplankton, stramenopiles often exhibited the highest relative abundances in mangrove, above-reef, off-reef, and open sea environments, where cyanobacteria also showed high relative abundances. Within stramenopiles, diatom amplicons dominated in salt ponds and mangroves, while dictyochophytes and pelagophytes prevailed above reefs and offshore. Green algae and cryptophytes were also present, and the former exhibited transitions following the gradient from inland to offshore. Chlorophytes and prasinophyte Class IV dominated in salt ponds, while prasinophyte Class II, including Micromonas commoda and Ostreococcus Clade OII, had the highest relative abundances of green algae in mangroves, above-reef, off-reef, and the open sea. To improve Class II prasinophyte classification, we sequenced 18S rRNA gene amplicons from the V4 region in 41 samples which were used to interrelate plastid-based results with information on uncultured prasinophyte species from prior 18S rRNA gene-based studies. This highlighted the presence of newly described Ostreococcus bengalensis and two Micromonas candidate species. Network analyses identified co-occurrence patterns between individual phytoplankton groups, including cyanobacteria, and heterotrophic bacteria. Our study reveals multiple uncultured and novel lineages within green algae and dictyochophytes in tropical marine habitats. Collectively, the algal diversity patterns and potential co-occurrence relationships observed in connection to physicochemical and spatial influences help provide a baseline against which future change can be assessed.